Experimental Study of the Corrosiveness of Ternary Blends of Biodiesel Fuel - Milano, Jassinnee; Umar, Hamdani; Shamsuddin, A. H.; Silitonga, A. S.; Irfan, Osama M.; Sebayang, A. H.; Fattah, I. M. Rizwanul; Mofijur, M. (Frontiers in Energy Research, 2021)
Biodiesel is an alternative renewable resource to petroleum-based diesel. The aim of using biodiesel is to reduce environmental pollution and combat global warming. Biodiesel application in compression ignition engines has shown its compatibility with better combustion characteristics and high engine performance. Many advantages can be obtained by using biodiesel, including reducing exhaust gases, reducing air toxicity, providing energy security, and being biodegradable. However, biodiesel's disadvantage involves oxidation stability, corrosion, degradation, and compatibility with other metallic materials. The present study investigates the corrosive behaviour of the ternary blends (waste cooking-Calophyllum inophyllum biodiesel-diesel) fuel that occurs in contact with mild steel and stainless steel 316. The observation study for mild steel and stainless steel 316 material under the static immersion method was performed for 7200 hr and 14400 hr, respectively, at room temperature (25-30 °C). In every 720 hr and 1440 hr of immersion time, the coupon’s profile was analysed by SEM/EDS, and the mass loss was observed, for corrosivity investigation. Based on the obtained results, the average corrosion rate of mild steel and stainless steel 316 is 0.6257nm/year and 0.0472nm/year at 7200 hr, respectively, the difference in corrosion rate for these metallic materials is approximately 92.46 %. The degradation of the fuel properties such as kinematic viscosity, density, refractive index, and acid value was monitored. In this study, stainless steel 316 was more resistant to corrosion attack with some micro pitting and showed better compatibility with the ternary blend than mild steel. The regression analysis and the correlation of corrosion rate were studied.